Um olhar complexo sobre a imagem do professor nas páginas da revista Veja no período do governo Lula (2003-2010) - Ribeiro, Cristiele Magalhães (2019)
The way of teaching has been changing along the centuries as well as the professionals’ representation and role regarding this area. Teachers had been already seen and treated as slaves, the ones who are the ‘knowledge holders’, disciplinarians, politics commentators and also as being the responsible ones for fulfilling the educational gaps left by family and society. The press, therefore, in its journalistic issues, makes up stereotypes and myths while it performs change and idealize this subject’s role herewith the others who are involved in the process of learning, sometimes praising or relativizing them. In view of that, the present work has as its general aim to know the professor representation at Veja Magazine along the govern of Luiz Inácio Lula da Silva (between 2003 and 2010), considering the production of senses. We wish to comprehend and explain how this professional’s image construction is made and analyse the idealization projected on him in the post published in this magazine which is among the world greatest circulation taker. For this purpose, we are making a research under qualitative imprint making usage of the complexity paradigm – from Edgar Morin – on methodological options as well as the speech analysis in the view of Eni Orlandi. The timing cutting was defined when we accomplished a pre research as we identified a greater concentration of periodicals on the education theme in this period. From the reports analysed, we could extract the following dimensions: the learning professor; the professor under the meritocratic system; the professor´s role; the sick and under pressure professor; and “leftist” professor. On the whole, the reports adopted a negative and ideological view characterizing professors as professionals who are uncommitted towards learning and their students. One who is unprepared, stressful and leftist politics based being considerably called lagged just like their defenders are. The more repetitive the image of this professional was when the publications advanced, more silent these subjects became. Positive examples – provided from other countries – were presented. However, there was no exemp lification of how they could be adaptable in Brazil. Instead of being plural by making the interlocution among different positions, discussions and voices, they were rather a partial vehicle by keeping their conservative politics positioning.